Penerapan Metode Bermain Peran Untuk Meningkatkan Kemampuan Berbicara Anak Pada Usia 5-6 Tahun di TK Dwi Karya Tanjung Kecamatan Koto Kampar Hulu - Lastri Lastri; Vitri Angraini Hardi; Citra Ayu (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This research was motivated by the low speaking ability of children aged 5-6 years at Dwi Karya Tanjung Kindergarten, Koto Kampar Hulu District. Therefore, researchers determined alternatives to improve the speaking skills of children aged 5-6 years at Dwi Karya Tanjung Kindergarten, Koto Kampar Hulu District. The research method used is Classroom Action Research (PTK). The data collection techniques used were observation, interviews and documentation. The data collection instrument used by researchers is the observation sheet. Data analysis in this classroom action research uses quantitative techniques. Based on the results of data analysis, it was concluded that: The results of increasing the use of the role-playing method were proven to be able to improve the speaking skills of children aged 5-6 years at Dwi Karya Tanjung Kindergarten. in cycle I continued to increase in cycle II.